ESTIMATION DE LA BIOMASSE AERIENNE DES ARBRES A TRONC NON CONFORME (CONTREFORTS) DES FORETS DU BASSIN CENTRAL CONGOLAIS PAR LA METHODE NON DESTRUCTRICE : CAS DES FORETS DE YASIKIA (OPALA/PROVINCE TSHOPO/RDC). - Lomba, Christophe B.; Janvier , LISINGO (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2022)
It is important to estimate the aerial biomass and the stocks of carbon of the trees to non compliant trunk in the forests of the Congolese central basin to plan the management of resources and to value the contribution of this forests in the attenuation of the effects of the climatic changes, and, it in the setting of the conservation to the scale of a reserve, that to Measure, to Return and to Verify the forests stocks of carbon in the setting of the national strategies for the Reduction of the Broadcasts of the GES bound to the Deforestation and the Deterioration of the forests (REDD+). This survey aimed the setting up of a protocol of evaluation of the aerial biomass and the stocks of corresponding carbon of the trees to particular architecture in the forest of Yasikia. To arrive there, a survey fine dendrometric has been done for all trees to non compliant trunk. The data dendrometric has been harvested on 189 trees left in 9 families and 20 species. The results of this survey show that it is preferable to use the equivalent diameter for a good evaluation of the biomass because the hold of diameter at the end of buttress or to the over, under esteem the quantity of biomass for a tree to non compliant trunk. The equation having permitted to estimate the woody biomass from different diameters was the one of Brown and al. (1989).